Weather Forecasting - Saifullah, Muhammad (IntechOpen, 2021)
Weather warnings are important because governments use them to protect life and property. In addition, predicting temperature and precipitation is important for agriculture. As such, weather forecasting is an integral part of meeting targets 2 and 13 of the United Nations' Sustainable Development Goals: zero hunger and climate action, respectively. This book presents recent developments in scientific research on weather and climate in the extreme environments of Asian, African, and European regions. It provides in-depth case studies from Pakistan, the United States, Vietnam, Nigeria, and Africa. The global and inter-disciplinary results of these studies help us to understand and address the grand challenges of weather as well as its impact on society.